Muamalah dalam Islam: Memahami Konsep 'Ariyah dan Aplikasinya - Suarni, Suarni (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The concept of 'Ariyah in Islam, within the framework of Muamalah (human interaction), holds a significant place in the social and economic aspects of Muslim life. This paper aims to explore the etymological and terminological dimensions of 'Ariyah and its practical implications in Islamic law. Employing a qualitative approach, this study draws on religious texts, including the Qur'an and Hadith, as well as scholarly works on Islamic jurisprudence. The analysis reveals that 'Ariyah, etymologically, is associated with the idea of borrowing and returning, and terminologically refers to the practice of utilizing another's possessions without compensation. This concept encompasses values of generosity and unconditional giving, with slight variations across Islamic schools of thought. The validity of 'Ariyah transactions in Islamic law depends on certain pillars and conditions, such as the declaration of borrowing, the ownership status of the lender and borrower, and the nature of the borrowed item. The concept of 'Ariyah aligns with the broader Islamic ethos of assistance and reciprocal cooperation, particularly in the practice of lending. Abstrak Konsep 'Ariyah dalam Islam, dalam kerangka Muamalah (interaksi manusia), memiliki tempat yang signifikan dalam aspek sosial dan ekonomi kehidupan Muslim. Tulisan ini bertujuan untuk mengeksplorasi dimensi etimologi dan terminologi dari 'Ariyah dan implikasi praktisnya dalam hukum Islam. Menggunakan pendekatan kualitatif, studi ini mengacu pada teks-teks agama, termasuk Al-Qur'an dan Hadits, serta karya-karya ilmiah tentang jurisprudensi Islam. Analisis mengungkapkan bahwa 'Ariyah, secara etimologi terkait dengan ide peminjaman dan pengembalian, dan secara terminologi merujuk pada praktik memanfaatkan kepemilikan orang lain tanpa kompensasi. Konsep ini mencakup nilai-nilai kemurahan hati dan pemberian tanpa syarat, dengan sedikit variasi lintas mazhab Islam. Keabsahan transaksi 'Ariyah dalam hukum Islam bergantung pada rukun dan syarat tertentu, seperti deklarasi peminjaman, status kepemilikan pemberi pinjaman dan penerima pinjaman, serta sifat barang yang dipinjam. Konsep 'Ariyah ini sejalan dengan etos Islam yang lebih luas tentang bantuan dan kerja sama timbal balik, terutama dalam praktik peminjaman.